PENGARUH PEMAHAMAN WAJIB PAJAK ORANG PRIBADI TERHADAP PENERAPAN SELF ASSESSMENT SYSTEM PADA KPP PRATAMA GORONTALO - Po'oe, Bambang Supriyanto; Amaliah, Tri Handayani; Tuli, Hartati (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2015)
Â Â This research aims to determine the influence of an individual taxpayer understanding of the Self Assessment System implementation on STO Gorontalo. The data in this study were taken from primary data through questionnaires. The number of samples used as subjects in this study were 100 individual taxpayer and using Convenience Sampling techniques. This study uses regression analysis simple.Â The results showed that the understanding of the individual taxpayer has a significant effect on the implementation of Self Assessment System. The determination coefficient show that 19.8% understanding of individual taxpayers influence the application of the Self Assessment System and the remaining 80.2% is influenced by other variables outside this study.